Motoneuron deafferentation and gliosis occur in association with neuromuscular regressive changes during ageing in mice. Issue 6 (20th July 2020) - Blasco, Alba; Gras, Sílvia; Mòdol‐Caballero, Guillem; Tarabal, Olga; Casanovas, Anna; Piedrafita, Lídia; Barranco, Alejandro; Das, Tapas; Pereira, Suzette L.; Navarro, Xavier; Rueda, Ricardo; Esquerda, Josep E.; et al.
Abstract: Background: The cellular mechanisms underlying the age‐associated loss of muscle mass and function (sarcopenia) are poorly understood, hampering the development of effective treatment strategies. Here, we performed a detailed characterization of age‐related pathophysiological changes in the mouse neuromuscular system. Methods: Young, adult, middle‐aged, and old (1, 4, 14, and 24–30 months old, respectively) C57BL/6J mice were used. Motor behavioural and electrophysiological tests and histological and immunocytochemical procedures were carried out to simultaneously analyse structural, molecular, and functional age‐related changes in distinct cellular components of the neuromuscular system. Results: Ageing was not accompanied by a significant loss of spinal motoneurons (MNs), although a proportion ( 15%) of them in old mice exhibited an abnormally dark appearance. Dark MNs were also observed in adult ( 9%) and young ( 4%) animals, suggesting that during ageing, some MNs undergo early deleterious changes, which may not lead to MN death. Old MNs were depleted of cholinergic and glutamatergic inputs ( 40% and 45%, respectively, P < 0.01), suggestive of age‐associated alterations in MN excitability. Prominent microgliosis and astrogliosis [ 93% ( P < 0.001) and 100% ( P < 0.0001) increase vs. adults, respectively] were found in old spinal cords, with increased density of pro‐inflammatory M1 microglia and A1 astroglia (25‐fold and 4‐fold increase, respectively, P < 0.0001). Ageing resulted in significant reductions in the nerve conduction velocity and the compound muscle action potential amplitude ( 30%, P < 0.05, vs. adults) in old distal plantar muscles. Compared with adult muscles, old muscles exhibited significantly higher numbers of both denervated and polyinnervated neuromuscular junctions, changes in fibre type composition, higher proportion of fibres showing central nuclei and lipofuscin aggregates, depletion of satellite cells, and augmented expression of different molecules related to development, plasticity, and maintenance of neuromuscular junctions, including calcitonin gene‐related peptide, growth associated protein 43, agrin, fibroblast growth factor binding protein 1, and transforming growth factor‐β1. Overall, these alterations occurred at varying degrees in all the muscles analysed, with no correlation between the age‐related changes observed and myofiber type composition or muscle topography. Conclusions: Our data provide a global view of age‐associated neuromuscular changes in a mouse model of ageing and help to advance understanding of contributing pathways leading to development of sarcopenia.